Two new species of the termitophilous rove beetle genus Xenogaster Wasmann from Brazil (Staphylinidae, Aleocharinae, Corotocini) - Pires-Silva, Carlos M. (Zootaxa, 2023)
Xenogaster Wasmann, 1891, is a Neotropical beetle genus of termitophilous beetles, comprising ten species disjunctly distributed. During the study of specimens of the Museu de Zoologia da Universidade de São Paulo, collected during expeditions to Southeastern Brazil, two new species were discovered. Xenogaster pseudonuda sp. nov. and X. kymopoleia sp. nov., are described and illustrated. A discussion is provided regarding the tarsal condition in Xenogaster and the coeloconic sensilla on antennomere III, constituting the first record for the subtribe Termitogastrina.